Pengaruh Iklim Sekolah terhadap Motivasi Guru dan Karyawan di SDN 005 Bandung - Edi Ahmad Junaedi; Elsa Sabinatun Nisa; Fauzan Nur Rohman; Nadia Widiyanti; Rosmaida Br Ginting; Siti Sarah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to determine the effect of school climate on the work motivation of teachers and employees at School 005 Bandung. School climate is the atmosphere or work environment created by relationships between school members, the principal's leadership, and applicable organizational policies. Teacher and employee work motivation significantly determines the success of the school's educational and administrative tasks. This study used a quantitative approach with a descriptive-verification method. Data collection was conducted through the distribution of questionnaires to teachers and employees at School 005 Bandung. Data analysis was conducted using a simple linear regression test to determine the extent of the influence of school climate on work motivation. The results indicate that school climate has a positive and significant influence on teacher and employee work motivation. The better the school climate, the higher the motivation of teachers and employees in carrying out their duties. This research provides important implications for managing a more conducive school climate to increase the work motivation of teachers and staff in achieving optimal educational goals.